QoE enhancements on satellite networks through the use of caches. (3rd July 2018) - Thibaud, Adrien; Fasson, Julien; Arnal, Fabrice; Pradas, David; Dubois, Emmanuel; Chaput, Emmanuel
Summary: A high throughput does not necessarily translate to a good Quality of Experience, especially in a satellite context. The round trip time, for instance, also has a tremendous impact on the reactivity of applications and thus on the Quality of Experience. Content delivery networks are massively used for over‐the‐top services in terrestrial network: They reduce the load of network and the delay as they draw the content closer to the end user. In a satellite system, the content delivery network presents a good opportunity for enhancing the end users' Quality of Experience and can change the conventional use of performance‐enhancing proxies. This paper investigates the satellite as access link for home networks or a backhaul link for small cells for a 5G perspective. We analysed the impact of caching on both gateway side and satellite terminal side for 2 on‐trend services: web browsing and adaptive video streaming (dynamic adaptive streaming over HTTP). The main contribution is an evaluation of transparent caching through a satellite platform. The caching policy is out of the scope of this paper. One large part of the testbed is based on an open‐source platform, OpenSAND that emulates the satellite system. To confirm the results, some real experiments have been conducted on a commercial satellite link. As expected, the transparent caching at the satellite terminal side can increase the Quality of Experience to its upper border as long as the content is available in the cache. For the satellite gateway cache, the performances exceed the expectations. Although the application experiences the satellite delay in this case, the traversal time of different Internet service provider networks also delays the delivery of content. Then it may have a greater impact on reactivity than the satellite itself. Through careful analysis of the different results, we noticed some issues. Transparent caching is unable to cache encrypted or dynamic content. Moreover, a misuse of caching can provoke bad behaviour of dynamic adaptive streaming over HTTP mechanisms and severely decrease the Quality of Experience. We designed a solution that in addition to solving the issue, alleviates the storage space of satellite terminal caches. Abstract : In this paper, we propose to use Content Delivery Network in a satellite network in order to enhance the Quality of Experience of end‐user. The major contribution of this study is to evaluate the impact of the placement of the caches for multiples applications (Web browsing and Adaptive video streaming). The experiences were made on an emulation tool and on a real satellite network.